Preventive Gabapentin versus Pregabalin to Decrease Postoperative Pain after Lumbar Microdiscectomy: A Randomized Controlled Trial - Mohsin Qadeer; Muhammad Waqas; Muhammad Jawad Rashid; Syed Ather Enam; Salman Sharif; Ghulam Murtaza (Asian Spine Journal, 2017)
Study DesignRandomized controlled trial.PurposeThe purpose of this study was to compare pregabalin and gabapentin for mean postoperative visual analog score (VAS) for pain in patients undergoing single-level lumbar microdiscectomy for intervertebral disc prolapse at a tertiary care hospital.Overview of LiteraturePregabalin has a superior pharmacokinetic profile and analgesic effect at lower doses than gabapentin; however, analgesic efficacy must be established during the perioperative period after lumbar spine surgery.MethodsThis randomized controlled trial was carried out at our institute from February to October 2011 on 78 patients, with 39 participants in each study group. Patients undergoing lumbar microdiscectomy were randomized to group A (gabapentin) or group B (pregabalin) and started on trial medicines one week before surgery. The VAS for pain was recorded at 24 hours and one week postoperatively.ResultsBoth groups had similar baseline variables, with mean ages of 42 and 39 years in groups A and B, respectively, and a majority of male patients in each group. The mean VAS values for pain at 24 hours for gabapentin vs. pregabalin were comparable (1.97±0.84 vs. 1.6±0.87, respectively; p=0.087) as were the results at one week after surgery (0.27±0.45 vs. 0.3±0.46, respectively; p=0.79). None of the patients required additional analgesia postoperatively. After adjusting for age and sex, the VAS value for group B patients was 0.028 points lower than for group A patients, but this difference was not statistically significant (p=0.817, R2=0.018).ConclusionsPregabalin is equivalent to gabapentin for the relief of postoperative pain at a lower dose in patients undergoing lumbar microdiscectomy. Therefore, other factors, such as dose, frequency, cost, pharmacokinetics, and side effects of these medicines, should be taken into account whenever it is prescribed.